Adjustment and Self-Esteem of Users and Nonusers of a University Counselling Service - Poirier, Pierre Paul; Tetreau, Bernard; Strobel, Michael (Canadian Journal of Counselling and Psychotherapy, 2012)
A Version of the Tennessee Self Concept Scale was used to measure self-esteem and adjustment in groups of users and nonusers of the counselling center at a French Canadian University. The sample of 110 male and 50 female college students was divided into subgroups of vocational-educational and personal-problem users and nonusers. Users were found to have significantly lower self-esteem scores than nonusers. When type of problem was controlled these differences appeared to be essentially due to the lower scores of the personal-problem groups. Sex seemed neither related to being a user nor to type of problem.